Prescription drug abuse - H.W. Wilson Company; Grey House Publishing, Inc. (Amenia, NY : Grey House Publishing, 2017)
In the modern world, physicians prescribe a multitude of medications, most derived from natural substances, to treat various bodily and mental disorders and some of the substances used also have a pleasurable neurological effect, creating a sense of euphoria, a tranquilizing effect, or intensifying alertness and focus. Over time, drug addiction and abuse has become a social justice and public health concern around the world. Governments have responded to addiction and drug abuse epidemics by banning the use of certain substances, but such efforts are not very efficacious and, instead, tend to result in the birth of black markets and criminal underworld industries involved in the production and distribution of illicit substances. In the 2010s, the drug crisis du jour in the United States involves the misuse and abuse of prescription drugs, substances developed as medications that have an intoxicating effect and so are also sought and used by individuals for recreation or to self-medicate. Because the supply of drugs cannot be completely eliminated without placing patients at risk, legislators, public health experts, and others working on the issue must struggle to balance the needs of patients with the effort to stem the tide of abuse. - Publisher/Preface
5: A search for solutions - policy -- The policy approach: restricting supply and legalizing treatment -- Researchers use black-market drug website to gauge public health / Felice J. Freyer -- Are pharmaceutical companies to blame for the opioid epidemic? / Alana Semuels -- Ohio sues five drugmakers, saying they fueled opioid crisis / Jeanne Whalen -- Congress probes West Virginia opioid shipments / Eric Eyre -- States require opioid prescribers to check for "doctor shopping" / Christine Vestal.
Includes bibliographical references (pages 207-210) and index.
Keywords: Medication abuse -- United States; Opioid abuse -- United States; Drug abuse -- United States